Energy Of Waqf: Overviewing Waqf's Potential In Driving Economic Growth In The Gorontalo Province - Sri Apriyanti Husan (Department of Islamic Accounting, Faculty of Islamic Economics and Business, IAIN Sultan Amai Gorontalo, 2021)
The demographic bonus that Gorontalo Province has as the population with the second largest Muslim percentage after Aceh, of course, can be a great potential in maximizing waqf collection in Gorontalo Province. So that later it is expected to encourage the acceleration of economic growth in Gorontalo Province. The purpose of this study is to find out how the potential of waqf in encouraging the acceleration of economic growth in Gorontalo Province. In this study, the researchers used qualitative research by conducting an exploratory study of the potential of waqf in encouraging the acceleration of economic growth in Gorontalo Province. The type of data used in this study consisted of primary data and secondary data. The data collection technique used in this research is the first interview. The second and third literature studies are by doing Subjective Intuitive. The results of this study indicate that waqf is an energy that can accelerate economic growth in Gorontalo Province. Although the process of maximizing the collection of waqf potential in Gorontalo Province will experience various challenges, there are 3 things that can be done to overcome these challenges. These 3 things are, first, the need to strengthen the social function of philanthropic institutions as institutions that collect and manage waqf assets. Second, the need for productive waqf management. Third, the inclusion of waqf awareness in educational institutions. For the sake of this implementation, of course, synergy is needed between related institutions such as the Indonesian Waqf Board, Philanthropic Institutions, Islamic Banks, Ministry of Religion, Ministry of Research, Technology and Higher Education, Ministry of Agriculture, Ministry of Education and Culture and other related institutions.